THE KINETICS OF OXYGEN EXCHANGE BETWEEN THE GEO4AL12(OH)24(OH2)128+(AQ) MOLECULE AND AQUEOUS SOLUTIONS - Lee A.P.; Phillips B.L.; Casey W.H. (My University, 2002)
We report rates of oxygen exchange with bulk solution for an aqueous complex, IVGeO4Al12(OH)24(OH2)128+(aq) (GeAl12), that is similar in structure to both the IVAlO4Al12(OH)24(OH2)127+(aq) (Al13) and IVGaO4Al12(OH)24(OH2)127+(aq) (GaAl12) molecules studied previously. All of these molecules have #-Keggin-like structures, but in the GeAl12 molecule, occupancy of the central tetrahedral metal site by Ge(IV) results in a molecular charge of +8, rather than +7, as in the Al13 and GaAl12. Rates of exchange between oxygen sites in this molecule and bulk solution were measured over a temperature range of 274.5 to 289.5 K and 2.95 < pH < 4.58 using 17O-NMR.Apparent rate parameters for exchange of the bound water molecules (η-OH2) are kex298 = 200 (+/-100) s-1, ΔH# = 46 (+/-8) kJ . mol-1, and ΔS# = -46 (+/-24) J . mol-1 K-1 and are similar to those we measured previously for the GaAl12 and Al13 complexes. In contrast to the Al13 and GaAl12 molecules, we observe a small but significant pH dependence on rates of solvolysis that is not yet fully constrained and that indicates a contribution from the partly deprotonated GeAl12 species.The two topologically distinct μ2-OH sites in the GeAl12 molecule exchange at greatly differing rates. The more labile set of μ2-OH sites in the GeAl12 molecule exchange at a rate that is faster than can be measured by the 17O-NMR isotopic-equilibration technique. The second set of μ2-OH sites have rate parameters of kex298 = 6.6 (+/-0.2) . 10-4 s-1, ΔH# = 82 (+/-2) kJ . mol-1, and ΔS# = -29 (+/-7) J . mol-1 . K-1, corresponding to exchanges ~40 and ~1550 times, respectively, more rapid than the less labile μ2-OH sites in the Al13 and GaAl12 molecules. We find evidence of nearly first-order pH dependence on the rate of exchange of this μ2-OH site with bulk solution for the GeAl12 molecule, which contrasts with Al13 and GaAl12 molecules.